A solvent-free polyurethane adhesive for electrical appliances and preparation method thereof

By modifying the surface treatment of silica, magnesium oxide and mica powder, and introducing specific ingredients into the polyurethane adhesive, the solvent-free polyurethane adhesive with high thermal stability and insulation properties is solved, the heat resistance in the prior art is solved The problem of insufficient properties and insulation performance achieves stable and electrical insulation effects in high temperature environments.

CN118406461BActive Publication Date: 2024-12-13GUANGDONG SINO-ADHESIVE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410562648.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2024-12-13
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

Existing polyurethane adhesives for electrical appliances have poor performance in terms of heat resistance and insulation performance, making it difficult to maintain stability in high temperature environments and ensure the normal operation and safety of electrical appliances.

Method used

Using the preparation method of solvent-free polyurethane adhesive, surface-modified silica, magnesium oxide and mica powder, and adding hexamethylene diisocyanate and iso-hydroxide on the basis of butyl hydroxyl glue and dimeric acid polyester polyol Components such as phoronediamine, DOPO-HQ and hydroxyPS microspheres form prepolymers with crosslinking structure and high thermal stability, and then add chain extenders, defoamers and dispersants, and stir through temperature control and speed control and ultrasonic dispersion to obtain finished adhesive products with excellent heat resistance and insulation properties.

Benefits of technology

The finished adhesive product produced has excellent heat resistance and insulation properties, can be maintained stable under high temperature environments, and improves compatibility and electrical insulation between polymers through the composite of modified inorganic particles, reducing electrical conductivity. to ensure the safe operation of electrical appliances.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a solvent-free polyurethane adhesive for electrical appliances and a preparation method thereof, and belongs to the technical field of adhesives. In the present invention, butyl hydroxyl rubber, dimer acid polyester polyol, hexamethylene diisocyanate, and isophorone diamine are selected as basic raw materials for reaction, hydroxyl PS microspheres are added as a part of the hard segment to provide a certain amount of heat capacity, and DOPO-HQ containing benzene rings and phenanthrene rings is introduced, so that the adhesive product obtained has excellent heat resistance. In addition, the present invention also performs surface modification on silicon dioxide, magnesium oxide, and mica powder with good insulating properties, and the modified three inorganic particles are compounded and added to the system as insulating fillers, so as to achieve a close compound between the insulating filler and the polymer. Since there are many defects and unsaturated bonds on the surface of the insulating filler, the carriers can be captured, thereby reducing its concentration, and then reducing the conductivity. Therefore, the obtained adhesive product can have outstanding insulating properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a solvent-free polyurethane adhesive for electrical appliances and a preparation method thereof. Background Art

[0002] Nowadays, electronic products have become an indispensable part of people's lives, and almost all electronic devices need to be assembled and fixed with adhesives. Since electronic products will dissipate heat and generate high temperatures during operation, and the components in electronic products may have short circuits or leakage, the adhesives used in electronic products are required to have heat resistance and insulation properties. This is to ensure that electronic products can still be firmly bonded in high temperature environments, and to ensure the normal operation and safety of electrical appliances. However, there are few heat-resistant and insulating adhesive products on the market, resulting in poor performance. The focus of most adhesive research and development is still on how to improve their viscosity. Therefore, it is particularly important to provide an adhesive product with excellent heat resistance and insulation. Summary of the invention

[0003] The purpose of the present invention is to provide a solvent-free polyurethane adhesive for electrical appliances and a preparation method thereof, which solves the problem of poor heat resistance and poor insulation performance in the existing polyurethane adhesive technology for electrical appliances.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a solvent-free polyurethane adhesive for electrical appliances, the preparation method specifically comprising the following steps:

[0006] S10, surface-modifying silicon dioxide, magnesium oxide and mica powder to obtain modified silicon dioxide, modified magnesium oxide and modified mica powder;

[0007] S20, controlling the temperature and pressure to vacuum dehydrate the butyl hydroxy rubber and dimer acid polyester polyol, cooling and adding hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate, controlling the temperature and stirring to react, and obtaining a prepolymer;

[0008] S30, sequentially adding chain extender, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, defoamer and dispersant to the prepolymer, stirring at controlled temperature and speed, then adding hydroxy PS microspheres, ultrasonically dispersing at controlled temperature, and vacuum degassing to obtain a finished adhesive.

[0009] As a preferred technical solution of the present invention, step S10 is specifically as follows:

[0010] S11, temperature-controlled vacuum drying of silicon dioxide to obtain dried silicon dioxide for standby use; deionized water and anhydrous ethanol are mixed evenly and the pH of the solution is adjusted to obtain a blended liquid A, the blended liquid A and KH570 are mixed and hydrolyzed at a controlled temperature to obtain a blended liquid B, the dried silicon dioxide is added to the blended liquid B for reaction in a controlled temperature water bath, suction filtered, washed, dried, ground, and sieved to obtain modified silicon dioxide;

[0011] S12, controlling the temperature to vacuum dry the magnesium oxide to obtain dried magnesium oxide for standby use; mixing KH550, deionized water and anhydrous ethanol for hydrolysis to obtain a blended liquid C, adding dried magnesium oxide to the blended liquid C for reaction in a temperature-controlled water bath, filtering, washing, drying, grinding and sieving to obtain modified magnesium oxide;

[0012] S13, controlling the temperature to vacuum dry the mica powder to obtain dried mica powder for later use; mixing KH550, deionized water and anhydrous ethanol for hydrolysis to obtain a blend liquid D, adding the dried mica powder to the blend liquid D for reaction in a controlled temperature water bath, filtering, washing, drying, grinding and sieving to obtain modified mica powder.

[0013] As a preferred technical solution of the present invention, the volume ratio of deionized water and anhydrous ethanol in step S11 is 1:2-5; the pH of the solution is adjusted to 3.5-4 using 0.1 mol / L hydrochloric acid solution; the dosage ratio of the blended liquid A and KH570 is 11-11.5 mL:1 g; the dosage ratio of the blended liquid B and the dried silica is 35-38 mL:1 g; and the particle size of the modified silica obtained after sieving is 400 nm.

[0014] As a preferred technical solution of the present invention, the dosage ratio of KH550, deionized water and anhydrous ethanol in step S12 is 0.2-0.3g:1mL:2-5mL; the dosage ratio of the blended liquid C and the dried magnesium oxide is 1-2mL:0.05-0.1g; and the particle size of the modified magnesium oxide obtained after sieving is 500nm.

[0015] As a preferred technical solution of the present invention, the dosage ratio of KH550, deionized water and anhydrous ethanol in step S13 is 0.15-0.3g:1mL:3-5mL; the dosage ratio of the blend liquid D and the dried mica powder is 1-2mL:0.05-0.1g; and the particle size of the modified mica powder obtained after sieving is 300nm.

[0016] As a preferred technical solution of the present invention, the temperature of the temperature control in steps S11-S13 is 80-85°C, the time of the vacuum drying is 30-35min; the time of the mixed hydrolysis is 30-35min; the temperature of the temperature-controlled water bath reaction is 80-85°C and the time is 1-2h; and the washing is done with deionized water.

[0017] As a preferred technical solution of the present invention, the mass ratio of the hydroxybutadiene rubber, dimer acid polyester polyol, hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate in step S20 is 50-60:20-25:20-30:10-15:0.02-0.05.

[0018] As a preferred technical solution of the present invention, the functionality of the hydroxybutadiene rubber in step S20 is 2.2, and the functionality of the dimer acid polyester polyol is 2.

[0019] As a preferred technical solution of the present invention, the temperature of the temperature-controlled and pressure-controlled vacuum dehydration in step S20 is 130-135°C, the pressure is 0.01MPa, and the time is 1-2h; the cooling is to 60°C; the temperature of the temperature-controlled stirring reaction is 100-105°C and the time is 1.5-2h.

[0020] As a preferred technical solution of the present invention, the mass ratio of the prepolymer, chain extender, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, defoamer, dispersant and hydroxy PS microspheres in step S30 is 10-12:1-1.05:1-1.1:0.2-0.3:0.1-0.2:0.15-0.2:0.02-0.04:0.03-0.05:0.3-0.4.

[0021] As a preferred technical solution of the present invention, the chain extender in step S30 is 1,4-butanediol; the defoaming agent is pentaerythritol stearate; and the dispersant is sodium polyacrylate.

[0022] As a preferred technical solution of the present invention, the particle size of the hydroxy PS microspheres in step S30 is 300 nm and is purchased from Beijing Zhongke Keyou Technology Co., Ltd.

[0023] As a preferred technical solution of the present invention, the temperature of the temperature-controlled and speed-controlled stirring in step S30 is 60-70°C, the speed is 10000-12000r / min, and the time is 10-20min; the temperature of the temperature-controlled ultrasonic dispersion is 60-70°C, and the time is 20-30min; the time of the vacuum defoaming is 30-35min.

[0024] Furthermore, the present invention also provides a finished adhesive product prepared by the preparation method.

[0025] Beneficial effects of the present invention:

[0026] (1) In the present invention, butyl hydroxyl rubber with a functionality of 2.2, dimer acid polyester polyol with a functionality of 2, hexamethylene diisocyanate, and isophorone diamine are selected as basic raw materials for reaction, so that a cross-linked structure exists in the system after the reaction, which increases the density of the finished adhesive and also enhances its heat resistance to a certain extent. In addition, the present invention also adds organic particles hydroxyl PS microspheres as part of the hard segment to provide a certain amount of heat capacity, so that the breaking of the carbamate bond in the system requires more heat. On this basis, DOPO-HQ containing benzene rings and phenanthrene rings is also introduced, and the greater rigidity of its functional groups helps to increase the thermal stability of the system. The finished adhesive thus obtained has excellent heat resistance.

[0027] (2) The present invention performs surface modification on silicon dioxide, magnesium oxide and mica powders with good insulating properties respectively, and compound the modified three inorganic particles and add them into the system as insulating fillers. The modified insulating fillers have improved compatibility with the system polymer, and achieve close compounding between the insulating fillers and the polymers. Since there are usually many defects and unsaturated bonds on the surface of the insulating fillers, the carriers can be captured, thereby reducing their concentration and further reducing the conductivity. Therefore, the obtained adhesive product can have outstanding insulating properties. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a solvent-free polyurethane adhesive for electrical appliances, the method for preparing the adhesive specifically comprising the following steps:

[0031] S10, surface-modifying silicon dioxide, magnesium oxide and mica powder to obtain modified silicon dioxide, modified magnesium oxide and modified mica powder, as follows:

[0032] S11, vacuum drying the silicon dioxide at 80°C for 35 minutes to obtain dried silicon dioxide for standby use; mixing deionized water and anhydrous ethanol at a volume ratio of 1:2 and adjusting the pH value of the solution to 3.5 with 0.1 mol / L hydrochloric acid solution to obtain a blended liquid A; mixing the blended liquid A and KH570 at a dosage ratio of 11.3 mL:1 g and controlling the temperature at 80°C for 35 minutes to obtain a blended liquid B; adding the dried silicon dioxide to the blended liquid B and controlling the temperature at 80°C for reaction in a water bath for 2 hours; filtering, washing with deionized water, drying, grinding, and sieving to obtain a modified silicon dioxide with a particle size of 400 nm;

[0033] The ratio of the blended liquid B to the dried silicon dioxide is 35 mL: 1 g;

[0034] S12, vacuum drying the magnesium oxide at 85°C for 30 min to obtain dried magnesium oxide for standby use; mixing KH550, deionized water and anhydrous ethanol at a dosage ratio of 0.25 g: 1 mL: 2 mL for 30 min to obtain a blended liquid C, adding dried magnesium oxide to the blended liquid C and controlling the temperature at 80°C in a water bath to react for 1 h, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified magnesium oxide with a particle size of 500 nm;

[0035] The dosage ratio of the blended liquid C and the dried magnesium oxide is 1 mL:0.08 g;

[0036] S13, vacuum drying the mica powder at 85°C for 30 minutes to obtain dried mica powder for standby use; mixing KH550, deionized water and anhydrous ethanol at a ratio of 0.3g:1mL:4mL for hydrolysis for 35 minutes to obtain a blended liquid D, adding the dried mica powder to the blended liquid D and reacting in a water bath at 80°C for 2 hours, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified mica powder with a particle size of 300nm;

[0037] The dosage ratio of the blended liquid D to the dried mica powder is 1 mL:0.05 g.

[0038] S20, controlling the temperature of butyl hydroxy rubber and dimer acid polyester polyol at 130° C. and the pressure at 0.01 MPa for vacuum dehydration for 1 h, then cooling to 60° C., adding hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate, controlling the temperature at 105° C. and stirring to react for 1.5 h to obtain a prepolymer;

[0039] The mass ratio of the butyl hydroxy rubber, dimer acid polyester polyol, hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate is 55:25:20:15:0.02; the functionality of the butyl hydroxy rubber is 2.2, and the functionality of the dimer acid polyester polyol is 2;

[0040] S30, add 1,4-butanediol, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, pentaerythritol stearate, and sodium polyacrylate to the prepolymer in sequence, control the temperature at 60°C and the speed at 11000 r / min, and stir for 10 min, then add hydroxyl PS microspheres with a particle size of 300 nm, control the temperature at 65°C and ultrasonically disperse for 30 min, and vacuum degas for 30 min to obtain a finished adhesive;

[0041] The mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified silicon dioxide, modified magnesium oxide, modified mica powder, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 11:1:1.05:0.2:0.1:0.15:0.02:0.04:0.3.

[0042] Example 2

[0043] A method for preparing a solvent-free polyurethane adhesive for electrical appliances, the method for preparing the adhesive specifically comprising the following steps:

[0044] S10, surface-modifying silicon dioxide, magnesium oxide and mica powder to obtain modified silicon dioxide, modified magnesium oxide and modified mica powder, as follows:

[0045] S11, vacuum drying the silicon dioxide at 85°C for 30 minutes to obtain dried silicon dioxide for standby use; evenly mixing deionized water and anhydrous ethanol at a volume ratio of 1:3.5 and adjusting the pH value of the solution to 4 with a 0.1 mol / L hydrochloric acid solution to obtain a blended liquid A, mixing the blended liquid A and KH570 at a dosage ratio of 11 mL:1 g and controlling the temperature at 83°C for 30 minutes to obtain a blended liquid B, adding the dried silicon dioxide to the blended liquid B and controlling the temperature at 83°C for reaction in a water bath for 1 hour, filtering, washing with deionized water, drying, grinding, and sieving to obtain a modified silicon dioxide with a particle size of 400 nm;

[0046] The ratio of the blend liquid B to the dried silicon dioxide is 37 mL: 1 g;

[0047] S12, vacuum drying the magnesium oxide at 80°C for 35 minutes to obtain dried magnesium oxide for standby use; mixing KH550, deionized water and anhydrous ethanol at a ratio of 0.2g:1mL:5mL for hydrolysis for 32 minutes to obtain a blended liquid C, adding dried magnesium oxide to the blended liquid C and controlling the temperature at 83°C in a water bath for reaction for 1 hour, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified magnesium oxide with a particle size of 500nm;

[0048] The ratio of the blended liquid C to the dried magnesium oxide is 1.5 mL:0.1 g;

[0049] S13, vacuum drying the mica powder at 83°C for 33 min to obtain dried mica powder for standby use; mixing KH550, deionized water and anhydrous ethanol at a ratio of 0.15 g: 1 mL: 3 mL for 30 min to obtain a blend D, adding the dried mica powder to the blend D and reacting in a water bath at 85°C for 1 h, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified mica powder with a particle size of 300 nm;

[0050] The dosage ratio of the blend liquid D to the dried mica powder is 1.5 mL:0.1 g.

[0051] S20, controlling the temperature of butyl hydroxy rubber and dimer acid polyester polyol at 135° C. and the pressure at 0.01 MPa for vacuum dehydration for 1 h, then cooling to 60° C., adding hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate, controlling the temperature at 100° C. and stirring for reaction for 2 h to obtain a prepolymer;

[0052] The mass ratio of the butyl hydroxy rubber, dimer acid polyester polyol, hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate is 50:20:25:10:0.03; the functionality of the butyl hydroxy rubber is 2.2, and the functionality of the dimer acid polyester polyol is 2;

[0053] S30, add 1,4-butanediol, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, pentaerythritol stearate, and sodium polyacrylate to the prepolymer in sequence, control the temperature at 65°C and the speed at 12000 r / min and stir for 15 minutes, then add hydroxy PS microspheres with a particle size of 300 nm, control the temperature at 70°C and ultrasonically disperse for 20 minutes, and vacuum degas for 32 minutes to obtain a finished adhesive;

[0054] The mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified silicon dioxide, modified magnesium oxide, modified mica powder, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 110:1.05:1.1:0.3:0.2:0.17:0.03:0.03:0.4.

[0055] Example 3

[0056] A method for preparing a solvent-free polyurethane adhesive for electrical appliances, the method for preparing the adhesive specifically comprising the following steps:

[0057] S10, surface-modifying silicon dioxide, magnesium oxide and mica powder to obtain modified silicon dioxide, modified magnesium oxide and modified mica powder, as follows:

[0058] S11, vacuum drying the silicon dioxide at 83°C for 30 minutes to obtain dried silicon dioxide for standby use; mixing deionized water and anhydrous ethanol at a volume ratio of 1:5 and adjusting the pH value of the solution to 4 with a 0.1 mol / L hydrochloric acid solution to obtain a blended solution A; mixing the blended solution A and KH570 at a dosage ratio of 11.5 mL:1 g and controlling the temperature at 85°C for 32 minutes to obtain a blended solution B; adding dried silicon dioxide to the blended solution B and controlling the temperature at 85°C for reaction in a water bath for 1 hour; filtering, washing with deionized water, drying, grinding, and sieving to obtain a modified silicon dioxide with a particle size of 400 nm;

[0059] The ratio of the blended liquid B to the dried silicon dioxide is 38 mL:1 g;

[0060] S12, vacuum drying the magnesium oxide at 83°C for 32 minutes to obtain dried magnesium oxide for standby use; mixing KH550, deionized water and anhydrous ethanol at a dosage ratio of 0.3 g:1 mL:3.5 mL for 35 minutes to obtain a blended liquid C, adding dried magnesium oxide to the blended liquid C and controlling the temperature at 85°C in a water bath to react for 2 hours, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified magnesium oxide with a particle size of 500 nm;

[0061] The dosage ratio of the blended liquid C and the dried magnesium oxide is 2 mL:0.05 g;

[0062] S13, vacuum drying the mica powder at 80°C for 35min to obtain dried mica powder for standby use; mixing KH550, deionized water and anhydrous ethanol at a ratio of 0.22g:1mL:5mL for hydrolysis for 33min to obtain a blended liquid D, adding the dried mica powder to the blended liquid D and reacting in a water bath at 83°C for 2h, filtering, washing with deionized water, drying, grinding and sieving to obtain a modified mica powder with a particle size of 300nm;

[0063] The dosage ratio of the blend liquid D to the dried mica powder is 2 mL:0.08 g.

[0064] S20, controlling the temperature of 132° C. and the pressure of 0.01 MPa to vacuum dehydrate the butyl hydroxy rubber and dimer acid polyester polyol for 2 h, then cooling to 60° C., adding hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate, controlling the temperature at 103° C. and stirring to react for 2 h to obtain a prepolymer;

[0065] The mass ratio of the butyl hydroxy rubber, dimer acid polyester polyol, hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate is 60:23:30:13:0.05; the functionality of the butyl hydroxy rubber is 2.2, and the functionality of the dimer acid polyester polyol is 2;

[0066] S30, add 1,4-butanediol, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, pentaerythritol stearate, and sodium polyacrylate to the prepolymer in sequence, control the temperature at 70°C and the speed at 10000 r / min and stir for 20 minutes, then add hydroxyl PS microspheres with a particle size of 300 nm, control the temperature at 60°C and ultrasonically disperse for 25 minutes, and vacuum degas for 35 minutes to obtain a finished adhesive;

[0067] The mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified silicon dioxide, modified magnesium oxide, modified mica powder, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 12:1.03:1:0.25:0.15:0.2:0.04:0.05:0.35.

[0068] Comparative Example 1

[0069] Compared with Example 1, the difference is that in step S30 of Comparative Example 1, hydroxy PS microspheres are not added, and the remaining operation steps and parameters are the same.

[0070] Comparative Example 2

[0071] Compared with Example 1, the difference is that DOPO-HQ is not added in step S30 of Comparative Example 2, and the remaining operation steps and parameters are the same.

[0072] Comparative Example 3

[0073] Compared with Example 1, the difference is that in step S30 of Comparative Example 3, modified silica is not added, and the mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified magnesium oxide, modified mica powder, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 12:1.03:1:0.28:0.32:0.04:0.05:0.35, and the remaining operating steps and parameters are the same.

[0074] Comparative Example 4

[0075] Compared with Example 1, the difference is that in step S30 of Comparative Example 4, modified magnesium oxide is not added, and the mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified silica, modified mica powder, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 12:1.03:1:0.32:0.28:0.04:0.05:0.35, and the remaining operating steps and parameters are the same.

[0076] Comparative Example 5

[0077] Compared with Example 1, the difference is that in step S30 of Comparative Example 5, modified mica powder is not added, and the mass ratio of the prepolymer, 1,4-butanediol, DOPO-HQ, modified silica, modified magnesium oxide, pentaerythritol stearate, sodium polyacrylate and hydroxy PS microspheres is 12:1.03:1:0.35:0.25:0.04:0.05:0.35, and the remaining operating steps and parameters are the same.

[0078] Test Example 1

[0079] The finished adhesive products obtained in Examples 1-3 and Comparative Examples 1-2 were used as samples for thermogravimetric testing using a differential thermal-thermogravimetric analyzer (TG), wherein the weight of the sample was 5 mg, the gas atmosphere was nitrogen, the heating rate was 15°C / min, the temperature range was 100-500°C, and the thermal decomposition temperature of each sample was shown in Table 1.

[0080] Table 1

[0081] Thermal decomposition temperature / ℃ Example 1 301.4 Example 2 297.1 Example 3 295.8 Comparative Example 1 210.6 Comparative Example 2 228.3

[0082] As can be seen from Table 1, the finished adhesive prepared in the present invention has excellent heat resistance. This is because the present invention adds organic particles of hydroxyl PS microspheres to assist as part of the hard segment to provide a certain amount of heat capacity, so that the rupture of the carbamate bond in the system requires more heat. On this basis, DOPO-HQ containing benzene rings and phenanthrene rings is also introduced to assist in increasing the thermal stability of the system with the greater rigidity of its functional groups, so that the finished adhesive prepared in this way has excellent heat resistance.

[0083] Test Example 2

[0084] The volume resistivity of the adhesive products obtained in Examples 1-3 and Comparative Examples 3-5 was tested according to standard ASTM D2739-1997. The larger the volume resistivity, the better the electrical insulation performance. The results are shown in Table 2.

[0085] Table 2

[0086] <![CDATA[Volume resistivity / (10 12 Ω·m)]]> Example 1 4.92 Example 2 4.89 Example 3 4.87 Comparative Example 3 4.29 Comparative Example 4 4.17 Comparative Example 5 4.20

[0087] As can be seen from Table 2, the adhesive product prepared by the present invention has outstanding insulation performance. This is because, in the present invention, silicon dioxide, magnesium oxide and mica powder with good insulation performance are correspondingly surface-modified, and the modified three inorganic particles are compounded and added to the system as insulating fillers. The modified insulating filler improves the compatibility with the system polymer, and achieves a close compound between the insulating filler and the polymer. Since there are usually more defects and unsaturated bonds on the surface of the insulating filler, the carriers can be captured, thereby reducing their concentration and further reducing the conductivity. Therefore, the obtained adhesive product can have outstanding insulation performance.

[0088] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0089] Various modifications or additions to the specific embodiments described or replacements in similar ways shall fall within the protection scope of the present invention as long as they do not deviate from the invention or exceed the scope defined by the claims.

Claims

1. A method for preparing a solvent-free polyurethane adhesive for electrical appliances, characterized in that: The preparation method specifically comprises the following steps: S10, surface-modifying silicon dioxide, magnesium oxide and mica powder to obtain modified silicon dioxide, modified magnesium oxide and modified mica powder; S20, controlling the temperature and pressure to vacuum dehydrate the butyl hydroxy rubber and dimer acid polyester polyol, cooling and adding hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate, controlling the temperature and stirring to react, and obtaining a prepolymer; The mass ratio of the butyl hydroxy rubber to dimer acid polyester polyol, hexamethylene diisocyanate, isophorone diamine and dibutyltin dilaurate is 50-60:20-25:20-30:10-15:0.02-0.05; S30, sequentially adding a chain extender, DOPO-HQ, modified silica, modified magnesium oxide, modified mica powder, a defoamer, and a dispersant to the prepolymer, stirring at a controlled temperature and speed, then adding hydroxy PS microspheres, performing temperature-controlled ultrasonic dispersion, and performing vacuum degassing to obtain a finished adhesive; The mass ratio of the prepolymer, chain extender, DOPO-HQ, modified silicon dioxide, modified magnesium oxide, modified mica powder, defoamer, dispersant and hydroxy PS microspheres is 10-12: 1-1.05: 1-1.1: 0.2-0.3: 0.1-0.2: 0.15-0.2: 0.02-0.04: 0.03-0.05: 0.3-0.

4.

2. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: The step S10 is specifically as follows: S11, temperature-controlled vacuum drying of silicon dioxide to obtain dried silicon dioxide for standby use; deionized water and anhydrous ethanol are mixed evenly and the pH of the solution is adjusted to obtain a blended liquid A, the blended liquid A and KH570 are mixed and hydrolyzed at a controlled temperature to obtain a blended liquid B, the dried silicon dioxide is added to the blended liquid B for reaction in a controlled temperature water bath, suction filtered, washed, dried, ground, and sieved to obtain modified silicon dioxide; S12, controlling the temperature to vacuum dry the magnesium oxide to obtain dried magnesium oxide for standby use; mixing KH550, deionized water and anhydrous ethanol for hydrolysis to obtain a blended liquid C, adding dried magnesium oxide to the blended liquid C for reaction in a temperature-controlled water bath, filtering, washing, drying, grinding and sieving to obtain modified magnesium oxide; S13, controlling the temperature to vacuum dry the mica powder to obtain dried mica powder for later use; mixing KH550, deionized water and anhydrous ethanol for hydrolysis to obtain a blend liquid D, adding the dried mica powder to the blend liquid D for reaction in a controlled temperature water bath, filtering, washing, drying, grinding and sieving to obtain modified mica powder.

3. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: The functionality of the hydroxybutane rubber in step S20 is 2.2, and the functionality of the dimer acid polyester polyol is 2.

4. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: The temperature of the temperature-controlled and pressure-controlled vacuum dehydration in step S20 is 130-135°C, the pressure is 0.01MPa, and the time is 1-2h; the cooling is to 60°C; the temperature of the temperature-controlled stirring reaction is 100-105°C and the time is 1.5-2h.

5. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: In step S30, the chain extender is 1,4-butanediol; the defoamer is pentaerythritol stearate; and the dispersant is sodium polyacrylate.

6. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: The particle size of the hydroxy PS microspheres in step S30 is 300 nm.

7. The method for preparing a solvent-free polyurethane adhesive for electrical appliances according to claim 1, characterized in that: In step S30, the temperature of the temperature-controlled and speed-controlled stirring is 60-70°C, the speed is 10000-12000 r / min, and the time is 10-20 min; the temperature of the temperature-controlled ultrasonic dispersion is 60-70°C, and the time is 20-30 min; the time of the vacuum degassing is 30-35 min.

8. An adhesive product obtained by the method for preparing a solvent-free polyurethane adhesive for electrical appliances as claimed in any one of claims 1 to 7.